Are too many safety measures crowding each other out?. (June 2018) - Abrahamsen, Eirik Bjorheim; Moharamzadeh, Alireza; Abrahamsen, Håkon Bjorheim; Asche, Frank; Heide, Bjørnar; Milazzo, Maria Francesca
Abstract: It is well known that investments in new safety measures do not always give the intended effect, as new safety measures are sometimes offset by behavioural changes. In this article, we show that another cause for a reduced effect is that competition for resources can lead new safety measures to crowd out existing measures; to demonstrate this, we use a case related to the unloading of LPG (Liquefied Petroleum Gas) at a warehouse. If this aspect is not taken into consideration, the effects of a single measure might be considered too high. An overinvestment in new safety measures might then occur.